The effect of parallel exercises of play employing a device designed to improve the accuracy and strength of the serving skill and forehand & backhand groundstrokes in tennis - Muhammad Rafid Mahdi (Peerian Journals Publishing, 2023)
This study aims to prepare parallel exercises employing a device designed to improve the accuracy and strength of the tennis player’s skills in terms of serve and forehand and backhand groundstrokes. The researcher used the experimental method given its suitability to the research problem. The research sample was purposefully selected, namely (12) players of Al-Jaysh Sports Club, equally divided into two groups: experimental (treatment) and control. Upon the concluding of the main experiment and tests, the SPSS program was used to process the data statistically to obtain the results, which were then presented and discussed. The researcher reached a number of important conclusions as the results showed that there are significant differences in statistical terms in the post-tests between the two groups set up in this study: control and experimental in the development of accuracy and strength of the serving skill and forehand and backhand groundstrokes in tennis and in favor of the experimental group. The researcher recommended the need to use modern training equipment given its positive impact on the development of skills in addition to increasing the excitement and suspense of the players.
Keywords: Parallel exercises of play; device designed; accuracy and strength of the serving skill